Overcoming nanoscale inhomogeneities in thin-film perovskites via exceptional post-annealing grain growth for enhanced photodetection - Du,T; Richheimer,F; Frohna,K; Gasparini,N; Mohan,L; Min,G; Xu,W; Macdonald,TJ; Yuan,H; Ratnasingham,SR; Haque,S; Castro,FA; et al. (Nano Letters: a journal dedicated to nanoscience and nanotechnology, 2022)
Antisolvent-assisted spin coating has been widely used for fabricating metal halide perovskite films with smooth and compact morphology. However, localized nanoscale inhomogeneities exist in these films owing to rapid crystallization, undermining their overall optoelectronic performance. Here, we show that by relaxing the requirement for film smoothness, outstanding film quality can be obtained simply through a post-annealing grain growth process without passivation agents. The morphological changes, driven by a vaporized methylammonium chloride (MACl)–dimethylformamide (DMF) solution, lead to comprehensive defect elimination. Our nanoscale characterization visualizes the local defective clusters in the as-deposited film and their elimination following treatment, which couples with the observation of emissive grain boundaries and excellent inter- and intragrain optoelectronic uniformity in the polycrystalline film. Overcoming these performance-limiting inhomogeneities results in the enhancement of the photoresponse to low-light (<0.1 mW cm–2) illumination by up to 40-fold, yielding high-performance photodiodes with superior low-light detection.